PENDAMPINGAN HUKUM TERHADAP ANAK DI BAWAH UMUR SEBAGAI KORBAN PENGANIAYAAN DALAM UPAYA RESTORATIVE JUSTICE - Anti Navirotul Baety; Aulia Vani Rahmawati; Dimas Andrianto Kusuma; Alif Farhan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Children as victims of abuse require comprehensive legal and psychosocial protection. This study discusses the importance of legal assistance for minors within the framework of restorative justice, an approach oriented towards recovery rather than mere punishment. Legal representatives play a role in ensuring that legal processes are fair and child-friendly, while psychosocial support helps restore the emotional and mental condition of child victims. This approach aligns with the principle of the best interests of the child, as outlined in various national and international regulations. The study's findings suggest that the synergy between legal and psychosocial assistance can strengthen child protection and enhance the effectiveness of case resolution through restorative pathways. However, challenges such as the lack of understanding among law enforcement officials and societal resistance remain obstacles to implementation. Therefore, efforts are needed to strengthen integrated support systems and cross-sector education to achieve comprehensive legal protection for children.